2022
DOI: 10.1016/j.jadohealth.2021.10.036
|View full text |Cite
|
Sign up to set email alerts
|

Association of Gender-Affirming Hormone Therapy With Depression, Thoughts of Suicide, and Attempted Suicide Among Transgender and Nonbinary Youth

Abstract: There are no large-scale studies examining mental health among transgender and nonbinary youth who receive gender-affirming hormone therapy (GAHT). The purpose of this study is to examine associations among access to GAHT with depression, thoughts of suicide, and attempted suicide among a large sample of transgender and nonbinary youth. Methods: Data were collected as part of a 2020 survey of 34,759 lesbian, gay, bisexual, transgender, queer, and questioning youth aged 13e24, including 11,914 transgender or no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(80 citation statements)
references
References 24 publications
(20 reference statements)
1
59
1
2
Order By: Relevance
“…Indeed, the notion of ROGD has been used by legislators to prohibit TGD youth from accessing gender-affirming medical Multiple studies have revealed that prohibiting TGD adolescents from accessing gender-affirming medical care would be expected to have detrimental impacts on TGD youth wellbeing. [16][17][18]22 The current study adds to the extant research arguing against the ROGD hypothesis by providing evidence inconsistent with the theories that (1) social contagion drives TGD identities, with unique susceptibility among AFAB youth, and…”
Section: Discussionmentioning
confidence: 59%
“…Indeed, the notion of ROGD has been used by legislators to prohibit TGD youth from accessing gender-affirming medical Multiple studies have revealed that prohibiting TGD adolescents from accessing gender-affirming medical care would be expected to have detrimental impacts on TGD youth wellbeing. [16][17][18]22 The current study adds to the extant research arguing against the ROGD hypothesis by providing evidence inconsistent with the theories that (1) social contagion drives TGD identities, with unique susceptibility among AFAB youth, and…”
Section: Discussionmentioning
confidence: 59%
“…Additionally, some trans and nonbinary people may take gender-affirming hormone treatments intentionally designed to alter their biological systems and improve mental health outcomes (Green et al, 2021). Transparent communication of health risks associated with hormone treatments is crucial to ensuring the health of all individuals.…”
Section: On the Inclusion Of Gender In Researchmentioning
confidence: 99%
“…The existing literature shows that access to affirming healthcare, hormone therapy, puberty suppression, and supportive communities are associated with improved mental health outcomes. 13,14 The authors cite sources to refute claims about the implications for improved mental health when access to gender-affirming healthcare is provided to TGD individuals. For example, Jorgensen et al highlight how puberty suppression alone has not been shown to improve symptoms of gender dysphoria, and they interpret this as no improvement in mental health outcomes.…”
Section: Mental Health Outcomes and Tgd Youthmentioning
confidence: 99%
“…Puberty suppression, followed by subsequent GAHT, in an affirming environment can improve gender dysphoria. 14 Additionally, one of the claims cited includes the necessity for data regarding mental health outcomes for adolescents with gender dysphoria matched with non-TGD peers with at least one co-existing mental health condition. This statement implies that gender dysphoria alone is a mental health condition, disregarding the source of mental health distress imposed by gender incongruence and societal pressures.…”
Section: Mental Health Outcomes and Tgd Youthmentioning
confidence: 99%
See 1 more Smart Citation